Efficacy and safety of elexacaftor plus tezacaftor plus ivacaftor versus tezacaftor plus ivacaftor in people with cystic fibrosis homozygous for F508del-CFTR: a 24-week, multicentre, randomised, double-blind, active-controlled, phase 3b trial. Issue 3 (March 2022) - Sutharsan, Sivagurunathan; McKone, Edward F; Downey, Damian G; Duckers, Jamie; MacGregor, Gordon; Tullis, Elizabeth; Van Braeckel, Eva; Wainwright, Claire E; Watson, Danie; Ahluwalia, Neil; Bruinsma, Bote G; Harris, Christopher; et al.
Summary: Background: Elexacaftor plus tezacaftor plus ivacaftor is a triple-combination cystic fibrosis transmembrane conductance regulator (CFTR) modulator regimen shown to be generally safe and efficacious in people with cystic fibrosis aged 12 years or older with at least one F508del-CFTR allele. We aimed to assess the magnitude and durability of the clinical effects of this triple combination regimen in people with cystic fibrosis homozygous for the F508del-CFTR mutation. Methods: We conducted a multicentre, randomised, double-blind, active-controlled, phase 3b trial of elexacaftor plus tezacaftor plus ivacaftor at 35 medical centres in Australia, Belgium, Germany, and the UK. Eligible participants were those with cystic fibrosis homozygous for the F508del-CFTR mutation, aged 12 years or older with stable disease, and with a percent predicted FEV1 of 40–90% inclusive. After a 4-week run-in period, in which participants received tezacaftor 100 mg orally once daily and ivacaftor 150 mg orally every 12 h, participants were randomly assigned (1:1) to receive 24 weeks of either elexacaftor 200 mg orally once daily plus tezacaftor 100 mg orally once daily plus ivacaftor 150 mg orally every 12 h (elexacaftor plus tezacaftor plus ivacaftor group) or tezacaftor 100 mg orally once daily plus ivacaftor 150 mg orally every 12 h (tezacaftor plus ivacaftor group). Randomisation was stratified by percent predicted FEV1, age at screening visit, and whether the participant was receiving CFTR modulators at the time of the screening visit. Patients, investigators, and sponsor's study execution team were masked to treatment assignment. The primary endpoint was the absolute change in Cystic Fibrosis Questionnaire-Revised (CFQ-R) respiratory domain score from baseline (ie, at the end of the tezacaftor plus ivacaftor run-in period) up to and including week 24. The key secondary endpoint was the absolute change from baseline in percent predicted FEV1 up to and including week 24; other secondary endpoints were the absolute change from baseline in sweat chloride concentrations up to and including week 24, and safety and tolerability. All endpoints were assessed in all randomised patients who had received at least one dose of their assigned regimen. This study is registered with ClinicalTrials.gov, NCT04105972 . Findings: Between Oct 3, 2019, and July 24, 2020, 176 participants were enrolled. Following the 4-week tezacaftor plus ivacaftor run-in period, 175 participants were randomly assigned (87 to the elexacaftor plus tezacaftor plus ivacaftor group and 88 to the tezacaftor plus ivacaftor group) and dosed in the treatment period. From baseline up to and including week 24, the mean CFQ-R respiratory domain score increased by 17·1 points (95% CI 14·1 to 20·1) in the elexacaftor plus tezacaftor plus ivacaftor group and by 1·2 points (−1·7 to 4·2) in the tezacaftor plus ivacaftor group (least squares mean treatment difference 15·9 points [95% CI 11·7 to 20·1], p<0·0001), the mean percent predicted FEV1 increased by 11·2 percentage points (95% CI 9·8 to 12·6) in the elexacaftor plus tezacaftor plus ivacaftor group and by 1·0 percentage points (−0·4 to 2·4) in the tezacaftor plus ivacaftor group (least squares mean treatment difference 10·2 percentage points [8·2 to 12·1], p<0·0001), and the mean sweat chloride concentration decreased by 46·2 mmol/L (95% CI 43·7 to 48·7) in the elexacaftor plus tezacaftor plus ivacaftor group and by 3·4 mmol/L (1·0 to 5·8) in the tezacaftor plus ivacaftor group (least squares mean treatment difference −42·8 mmol/L [–46·2 to −39·3], nominal p<0·0001). Most participants (70 [80%] in the elexacaftor plus tezacaftor plus ivacaftor group and 74 [84%] in the tezacaftor plus ivacaftor group) had adverse events that were mild or moderate in severity; serious adverse events occurred in five (6%) of 87 participants in the elexacaftor plus tezacaftor plus ivacaftor group and 14 (16%) of 88 participants in the tezacaftor plus ivacaftor group. One (1%) participant in the elexacaftor plus tezacaftor plus ivacaftor group discontinued treatment due to an adverse event of anxiety and depression. Two (2%) participants in the tezacaftor plus ivacaftor group discontinued treatment due to adverse events of psychotic disorder (n=1) and obsessive-compulsive disorder (n=1). Interpretation: The elexacaftor plus tezacaftor plus ivacaftor regimen was safe and well tolerated, and led to significant and clinically meaningful improvements in respiratory-related quality of life and lung function, as well as improved CFTR function, changes that were durable over 24 weeks and superior to those seen with tezacaftor plus ivacaftor in this patient population. Funding: Vertex Pharmaceuticals.